Mandapa of the Mahakal Temple - Temples of India Project Team (Jio Institute, 2024)
The mandapa of the temple is open and has only base mouldings belonging to the old structure. It now has a smooth tile floor and there are two broad stairs at the end which lead to the main sanctum. A black stone figure of nandi facing the sanctum is placed on one of the stairs. The front wall of the main sanctum is also a new structure with a metal gate to enter the sanctum. The udumbar (threshold) of the sanctum has the original part of the temple which now is the only decorative element left of the entire façade.